Yona of the dawn. 37 - Kusanagi, Mizuho, 1979- (Shojo beat manga., 2022)
Princess Yona lives an ideal life as the only princess of her kingdom. Doted on by her father, the king, and protected by her faithful guard Hak, she cherishes the time spent with the man she loves, Su-won. But everything changes on her 16th birthday when tragedy strikes her family! Emperor Chagol's wily concubine Meinyan encounters Hak in a Hiryuu Palace prison cell! When Hak turns down her offer to escape together, what will Meinyan's next move be? Meanwhile, tension mounts in South Kai, where Emperor Chagol is still waiting for Meinyan's return from Kohka!